2008
DOI: 10.1016/j.ijgo.2008.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity following hysterectomy in Egypt

Abstract: As women undergoing hysterectomy risk psychiatric morbidity, gynecologists should consider less invasive interventions to treat benign conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
(20 reference statements)
1
18
1
Order By: Relevance
“…Our study results are consistent with previous studies showing that hysterectomy is associated with depression (Helmy et al, 2008;Jawor et al, 2001). In a two-year prospective observational study in Egypt, Helmy et al found an increase in the risk of depression in women who undergo hysterectomy for benign conditions, whether they had psychiatric comorbidity before surgery or not (Helmy et al, 2008).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our study results are consistent with previous studies showing that hysterectomy is associated with depression (Helmy et al, 2008;Jawor et al, 2001). In a two-year prospective observational study in Egypt, Helmy et al found an increase in the risk of depression in women who undergo hysterectomy for benign conditions, whether they had psychiatric comorbidity before surgery or not (Helmy et al, 2008).…”
Section: Discussionsupporting
confidence: 94%
“…In a two-year prospective observational study in Egypt, Helmy et al found an increase in the risk of depression in women who undergo hysterectomy for benign conditions, whether they had psychiatric comorbidity before surgery or not (Helmy et al, 2008). However, other studies have reported no negative effects on the psychological condition of women after hysterectomy performed for non-malignant causes (Darwish et al, 2014;Farquhar et al, 2008;Gibson et al, 2012;Persson et al, 2010;Yen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a significant difference would be obtained with larger sample sizes. On the other hand, losing one's maternal role within the family can adversely affect gender identity, sexuality, marital relations, and self-esteem [22] in Egypt. It is therefore also possible that the infertile women in our study maintained an interest in a normal sexual relationship-even with less frequent encounters and a diminished satisfaction-to compensate for the loss of their maternal role.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Egypt found 42.9% respondents were illiterate, 28.6% completed primary, 17.1% completed secondary and 11.3% completed graduation. 16 An Indian study also found that, majority (62%) of the respondents were illiterate. 15 Regarding the psychiatric disorders the current study revealed that, psychiatric disorders were present in 38.3% of hysterectomized women while in control group it was 28.1%.…”
Section: Resultsmentioning
confidence: 90%